Physical functionality in the daily life of the elderly in Azogues - Gloria Luzmila Pogyo Morocho; Andrés Alexis Ramírez Coronel; Isabel Cristina Mesa Cano; Marcia Verónica Pogyo Morocho (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2023)
Aging is a stage in which there are morpho-physiological changes that affect the functional capacity and significantly influence their well-being. The main objective was to determine the sociodemographic and clinical factors associated with the physical functionality of the elderly in the popular medical center of Azogues, with the purpose of generating a nursing action plan. Methodology: Quantitative, correlational, cross-sectional, retrospective study. With a population of 243 clinical histories of older adults 2019-2020, sociodemographic data, morbidity and performance of basic and instrumental activities of daily living were evaluated, in relation to clinical variables, most of the population studied did not present any pathology, but it is important to note that there are important data on arterial hypertension and diabetes mellitus, and these results should be considered for future research or action plans for these groups. The evaluation of the functionality of basic activities yielded important data equivalent to the need for help to perform basic activities, as well as the application of the Lawton and Brody Scale, which showed the need for support to perform instrumental activities, and the evaluation of geriatric depression showed mild depression. Conclusion: The functional capacity of the elderly in the Centro Médico Popular de Azogues is determined by age, sociodemographic characteristics and nutritional evaluation; generating an opportunity for intervention at the primary level of the elderly.